DEFINITION AND TYPES OF INTERNATIONALISMS - Ruziev Khusniddin Bakhritdinovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article discusses internationalisms and their main types in the English language. It explains how internationalisms originate from different languages and spread through historical and cultural contact. The study briefly outlines key periods of lexical borrowing into English. It also emphasizes the role of internationalisms in modern global communication.